Contribution of T.M. Hasbi Ash-Shiddieqy in the Renewal of Islamic Law in Indonesia - Asy'ari Asy'ari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
T.M. Hasbi ash-Shiddieqy is one of the leading reformers of Islamic law in Indonesia. He initiated the idea to draft Islamic law in accordance with the socio-culture of Indonesian society called "Fiqh Indonesia". According to T.M Hasbi ash-Shiddieqy law that applies in Indonesia does not follow Indonesian society's personality. Therefore, he emphasized the need to make laws that follow Indonesia's socio-cultural society and follow the conditions and developments of the times. As for the Ijtihad of the previous scholars contained in the fiqh, madhab is not necessarily discarded but chosen in accordance with the socio-cultural conditions of Indonesian society. In expressing his opinion, T.M Hasbi ash-Shiddieqy uses a textual and contextual approach based on urf, mashlahah mursalah and sadd adz-dzari'ah. Among the ideas of renewal of T.M. Hasbi ash-Shiddieqy is collective, allowing shaking hands with non-mahram women (women who have no blood relation), zakat (tax) non-Muslims, the establishment of zakat board institutions, the ability to make pictures and statues, the use of hisab methods in determining the beginning of Ramadan and the law of cutting hands because it is continuously repeated not due to the level of stolen goods.